Tribology of Machine Elements Fundamentals and Applications - Pintaude, Giuseppe; Cousseau, Tiago; Rudawska, Anna (IntechOpen, 2022)
Tribology is a branch of science that deals with machine elements and their friction, wear, and lubrication. Tribology of Machine Elements - Fundamentals and Applications presents the fundamentals of tribology, with chapters on its applications in engines, metal forming, seals, blasting, sintering, laser texture, biomaterials, and grinding.